18F-NaF PET/CT Findings in Fibrous Dysplasia. (November 2015) - Lee, Hyunjong; Lee, Kyu Sang; Lee, Won Woo
<x xml:space="preserve">Abstract</x> Abstract A 43-year-old woman with breast cancer underwent 99mTc-hydroxymethylene diphosphonate bone scintigraphy for preoperative workup. An abnormal lesion with increased uptake was found in the right humeral shaft, and 18F-NaF bone PET/CT was performed for clarification. There was high uptake of 18F-NaF without cortical bone disruption in the right humeral shaft, corresponding to the site on bone scintigraphy. Upper arm MRI was performed subsequently, and metastasis was suggested as a differential diagnosis. However, this lesion was pathologically diagnosed as fibrous dysplasia after curettage surgery.